Effectiveness of Padlet-Supproted Problem-Based Learning for Biology Students’ Critical Thinking - Sifak Indana; Ahmad Basri; Dian Permatasari Kusuma Dayu; Nur Ainiyah (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2026)
Developing students’ critical thinking skills remains a major challenge in higher education, particularly in biology learning, which requires strong analytical and evaluative abilities. The integration of hypermedia such as Padlet within a Problem-Based Learning (PBL) framework has the potential to create interactive and collaborative learning environments that support higher-order thinking. This study aimed to examine the effectiveness of Padlet hypermedia integrated with Problem-Based Learning in enhancing the critical thinking skills of Biology Education students. A quasi-experimental design with a non-equivalent control group was employed involving 60 undergraduate students from the Biology Education program at Surabaya State University. The participants were divided into an experimental group (n = 30) using Padlet-based PBL and a control group (n = 30) using Google Classroom. Data were collected through validated open-ended tests of critical thinking skills, supported by questionnaires and classroom observations. The data were analysed using normality and homogeneity tests, N-gain analysis, and an independent samples t-test. The results showed that students in the experimental group achieved significantly higher critical thinking scores than those in the control group (p = 0.003). The experimental group also demonstrated greater improvement from pre-test to post-test, indicating stronger development in problem analysis, information evaluation, inference, and logical reasoning. These findings suggest that Padlet hypermedia integrated with Problem-Based Learning may provide a more effective learning environment for promoting students’ critical thinking skills through interactive, collaborative, and reflective learning processes.